The formaldehyde stress on photosynthetic efficiency and oxidative stress response of moss Racomitrium japonicum L. - Li, Wanting; Zhang, Jiawen; Ma, Siqi; Zhou, Min; Li, Ruixin; Tang, Hao; Qiu, Haiyan; Ren, Peng; Tang, Yunlai; Lu, Yunmei; Huang, Renhua; Chen, Ke (Frontiers in Plant Science, 2025)
IntroductionFormaldehyde is a common gaseous pollutant emitted by buildings and decorative materials. In recent years, growing concerns have been raised regarding its harmful effects on health in indoor air. Therefore, this study aims to investigate the physiological and photosynthetic response mechanisms of Racomitrium japonicum under formaldehyde stress.MethodsR. japonicum was exposed to dynamic fumigation with formaldehyde for 7 days, with each day comprising an 8-h exposure period within a sealed container. The effects on plant structure, pigment content, photosynthetic efficiency, and reactive oxygen species (ROS) generation were assessed.Results and discussionOur findings revealed that formaldehyde stress caused structural damage, reduced pigment content, decreased photosynthetic efficiency, and increased ROS production in R. japonicum. Significantly, distinct stress-response pathways were observed at different formaldehyde concentrations. In response to low and moderate formaldehyde concentrations, R. japonicum activated its antioxidant enzyme system to mitigate ROS accumulation. In contrast, the high-concentration treatment group demonstrated suppressed antioxidant enzyme activity. In response, R. japonicum used nonphotochemical quenching and activated cyclic electron flow to mitigate severe cellular damage. This study provides an in-depth understanding of the physiological changes in R. japonicum under formaldehyde stress, elucidating its response mechanisms. The findings offer valuable insights for developing effective indoor formaldehyde monitoring and purification methods.